Preliminary investigation of the student-delivered Community Outreach teleheAlth program for Covid education and Health promotion (COACH). (28th July 2022) - Yang, Michelle C; Clayton, Cam; Harris, Devin; Pelletier, Chelsea; Schmidt, Julia; Zwicker, Jill G; Sakakibara, Brodie M
Abstract: Background: COVID-19 public health restrictions (i.e. physical distancing) compromise individuals' ability to self-manage their health behaviours and may increase the risks of adverse health events. Objectives: To evaluate the student-delivered Community Outreach teleheAlth program for Covid education and Health promotion (COACH) on health-directed behaviour (self-management) among older adults (≥65 years of age, n = 75). Secondary objectives estimated the influence of COACH on perceived depression, anxiety, and stress; social support; health-related quality of life; health promotion self-efficacy; and other self-management domains. Methods: COACH was developed to provide chronic disease management and prevention support among older adults via telephone or videoconferencing platforms (i.e. Zoom). In this single-group, pre-post study, our primary outcome was measured using the health-directed behaviour subscale of the Health Education Impact Questionnaire. Secondary measures included the Depression, Anxiety and Stress Scale, Medical Outcomes Study: Social Support Survey, MOS Short Form-36, and Self-Rated Abilities for Health Practices Scale. Paired sample t -tests were used to analyse outcome changes. Results: Mean age of participants was 72.4 years (58.7% female; 80% ≥2 chronic conditions). Health-directed behaviour significantly improved after COACH ( P < 0.001, d = 0.45). Improved health promotion self-efficacy ( P < 0.001, d = 0.44) and decreased mental health were also observed ( P < 0.001, d = −1.69). Discussion: COACH likely contributed to improved health-directed behaviour and health promotion self-efficacy despite the diminished mental health-related quality of life during COVID-19. Our findings also highlight the benefits of using health professional students for the delivery of virtual health promotion programs. Clinical Trial Information: ClinicalTrials.gov ID: NCT04492527